Determining the Change in Retail Prices of Veal in Turkey by GARCH Method Between 2014-2017 - Arikan, Mehmet Saltuk; Cevrimli, Mustafa Bahadir; Akin, Ahmet Cumhur; Tekindal, Mustafa Agah (Kafkas Univ, Veteriner Fakultesi Dergisi, 2019)
In Turkey, the demand for veal in the red meat market is steadily increasing. In the formation of this demand and price; additional factors such as consumer preferences, government interventions in the red meat market, import decisions, also the implemented policies and subsidies are effective besides the main factors. However, the fact that such practices do not affect the veal prices in the market makes it impossible to ensure price stability and a sustainable market. The analysis of the change in retail prices is important for both producers and consumers so that the validity of this view can be tested. The aim of this study was to analyze the retail prices of minced meat and the veal cubes from the first week of January 2014 to the last week of December 2017 via using the volatility estimation modeling method in the context of the effectiveness of the policies and market interventions applied in the red meat sector implemented in Turkey. Non-stationary series were made stationary by differencing. By developing a Generalised Autoregressive Conditional Heteroskedasticity (GARCH 1,1) model using the series subject to a unit root test, it was found to be the optimal model that best explains the fluctuation of the prices. The results of the estimation show that the retail prices of veal cubes and minced meats fluctuated conspicuously in the said period and that the implemented policies and the market interventions were not adequate to eliminate the instability and uncertainty of the prices.
Türkiye’de perakende dana eti fiyatlarındaki değişimin garch yöntemiyle belirlenmesi, 2014-2017
4th International Congress on Veterinary and Animal Science -- JUL 12-15, 2018 -- Nevsehir, TURKEY
Keywords: GARCH; Price volatility; Time series; Turkey; Veal